The Palgrave Handbook of Biology and Society (Palgrave Macmillan UK, 2018)
This comprehensive handbook synthesizes the often-fractured relationship between the study of biology and the study of society. Bringing together a compelling array of interdisciplinary contributions, the authors demonstrate how nuanced attention to both the biological and social sciences opens up novel perspectives upon some of the most significant sociological, anthropological, philosophical and biological questions of our era. The six sections cover topics ranging from genomics and epigenetics, to neuroscience and psychology to social epidemiology and medicine. The authors collaboratively present state-of-the-art research and perspectives in some of the most intriguing areas of what can be called biosocial and biocultural approaches, demonstrating how quickly we are moving beyond the acrimonious debates that characterized the border between biology and society for most of the twentieth century. This landmark volume will be an extremely valuable resource for scholars and practitioners in all areas of the social and biological sciences. The chapter 'Ten Theses on the Subject of Biology and Politics: Conceptual, Methodological, and Biopolitical Considerations' is open access under a CC BY 4.0 license via link.springer.com. Versions of the chapters 'The Transcendence of the Social', 'Scrutinizing the Epigenetics Revolution', 'Species of Biocapital, 2008, and Speciating Biocapital, 2017' and 'Experimental Entanglements: Social Science and Neuroscience Beyond Interdisciplinarity' are available open access via third parties. For further information please see license information in the chapters or on link.springer.com.